Leadership Patterns in the Digital Era - Adzani, Adinda Muthia; Bahiroh, Eloh (PT FORMOSA CENDEKIA GLOBAL, 2024)
In this digital change, digital leaders are needed who can drive faster transformation within the organization. This research aims to further analyze leadership patterns in the digital era. This research uses a qualitative approach, using the literature review method. This study was conducted to examine the role of digital leadership in the government sector in realizing digital transformation. The presence of this digital leader can encourage accelerated transformation within the organization.